2011
DOI: 10.1002/hbm.21460
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral data and neural correlates for postural prioritization and flexible resource allocation in concurrent postural and motor tasks

Abstract: This study was undertaken to investigate the reciprocity effect between postural and suprapostural performances and its underlying neural mechanisms wherein subjects executed a perceptual-motor suprapostural task and maintained steady upright postures. Fourteen healthy individuals conducted force-matching maneuvers (static vs. dynamic) under two stance conditions (bipedal stance vs. unipedal stance); meanwhile, force-matching error, center of pressure dynamics, event-related potentials (ERPs), and the movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…Previous dual task balance studies [43] [45] have found older adults tend to prioritize the motor tasks (i.e. postural control, and balance recovery on a moving platform) and perform significantly worse in cognitive tasks in dual task conditions.…”
Section: Discussionmentioning
confidence: 87%
“…Previous dual task balance studies [43] [45] have found older adults tend to prioritize the motor tasks (i.e. postural control, and balance recovery on a moving platform) and perform significantly worse in cognitive tasks in dual task conditions.…”
Section: Discussionmentioning
confidence: 87%
“…Postural control mechanisms depend on sensory information received from the visual, proprioceptive, and vestibular systems as well as appropriate motor outputs. As postural conditions become more challenging (e.g., standing on a narrow support, unipedal stance, or even dual-tasking), regions including the prefrontal cortex (PFC; Mihara et al, 2008) and parietal lobes (Mihara et al, 2008; Huang and Hwang, 2013) become progressively more involved in its monitoring. An increase in cortical involvement has been demonstrated in normal aging (Zwergal et al, 2012; Sullivan et al, 2009), especially during challenging conditions (Goble et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the concurrent execution of unrelated visual perception and working memory tasks, beta oscillation (18–24 Hz) was enhanced over that in the single-task condition, functionally serving to interface frontal-executive and occipitoparietal-perceptual processes [ 19 ]. Our previous work on a posture-motor task also revealed that ERPs in the fronto-parietal networks are important in monitoring of the attentional states in a postural-suprapostural task [ 20 , 21 ]. While maintaining upright stance and performing a force-matching task (a motor-suprapostural task), N1 negativity varied positively with the level of postural instability [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work on a posture-motor task also revealed that ERPs in the fronto-parietal networks are important in monitoring of the attentional states in a postural-suprapostural task [ 20 , 21 ]. While maintaining upright stance and performing a force-matching task (a motor-suprapostural task), N1 negativity varied positively with the level of postural instability [ 20 , 21 ]. This N1 negativity of posture-related ERP is thought to originate in the fronto-central regions [ 22 ], and to be relayed to anticipatory arousal [ 23 ] and sensory processing of postural perturbation [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation